Evaluación del sistema gerencial y su incidencia en el proceso administrativo de la Dirección Distrital de Salud 23D02 Santo Domingo, periodo 2013-2014 - Ramírez Sánchez, Luis Felipe (2015)
This research study was developed in the Health District No. 23D02. This decentralized agency of the Ministry of Public Health is located in Canton Santo Domingo in the Bomboli Parish, Street: Av Esmeraldas and the Búa Road. The Ministry of Health aims to strengthen its actions from the first level of care. It is necessary for the right to health is guaranteed, state institutions strengthen their intervention priority fluidity in your processes. We have detected certain critical points in the Administrative Process 23D02 Health District. With the present investigation is achieved confirm this observation and causes of the problems are sought. Subsequently, based on the weaknesses found, a proposed strategic plan with the aim of providing a tool to help manage the administrative process was designed. Among the most significant weaknesses they were found was: low levels of leadership, scarcity of resources to implement the planning processes, lack of space for communication, and lack of mechanisms for conflict resolution. Based on these identified issues, designing a strategic plan, which proposes an action plan with strategies to boost the efficiency of the equipment. The research focused on the impact that has in the Administrative Process Management District 23D02. To assess the impact tools that allowed collecting data on compliance with achieved results and determine the weaknesses that exist in both the management and the administrative process was applied. With this study it was possible to evaluate the Management System and the incidence in the administrative process is determined. Therefore, the Strategic Plan focuses on leadership and management actions to increase compliance and strengthen results teamwork within he Health District. Keywords: Assessment, Management System, Administrative Process